Understanding Shape Memory Alloy Torsional Actuators: From the Conceptual to the Preliminary Design - Mario Sansone; Salvatore Ameduri; Antonio Concilio; Enrico Cestino (Actuators, 2022)
Shape memory alloy actuators have been studied for more than thirty years. Many experimental tests have been performed, and several patents have been registered. However, designing such devices is still a challenging task. On the one hand, models are not yet able to provide the accuracy required to replace a substantial portion of the experimental tests; on the other hand, it seems that a gap exists in the literature between the main ideas behind SMA torsional actuators and their actual implementation. This work is a systematic effort to fill this gap, helping researchers and designers in developing SMA torsional actuators with a particular focus on aeronautical applications. This paper reports all the steps toward the preliminary design of such devices, using a state-of-the-art, commercially available FEM software. Moreover, the SMA rods’ behaviour under mechanical and thermal loading is thoroughly examined, looking at monitoring stress, temperature, torque and martensite evolution simultaneously, and thus providing a holistic vision of the macroscopic phenomena involved during phase transformations. Simple aerodynamic load predictions are also performed, using Xfoil for three classes of aircraft (medium size UAV, Four-Seat Aircraft and Regional Transport Aircraft).